Orígenes de la Cristología del Cuarto Evangelio: El problema de la unidad literaria y teológica - Carbullanca Núñez, César (Veritas, 2010)
The article seeks illuminate the discussion of the unit literary and theological of the fourth gospel. More provocative, Do we find one or several christologies in the Fourth Gospel? This research delivery a gaze overview of the response given by the defenders of the theory strata to the question of the unit literary and theological the Gospel of John, placing in evidence that the issue literary is linked to a different Christology proposal by these authors. The solutions given by the authors ranging from the existence of traditions or a Vorlage, as a resource to a Grundschrift or Semeia Quelle and some hybrid solutions. In Parallel these proposals show various christologies, thus, for example, the figure of a Jesus as Theios aner, Son of God or the mosaic prophet. The theory of the strata has received since its initiation a series of objections of various kinds, calling as insufficient and arbitrary, arguing the need to look for a new synthesis of the studies johannine.